Using the morphological chart technique for the design of polymeric-based composite automotive pedals - Salit, Mohd Sapuan (2006)
In this paper, a study of using the morphological chart in idea generation for the polymeric-based composite automotive pedal box system is presented. The application of the morphological charts enabled designers to identify the sub-solutions to each sub-functions of the design. For example, in accelerator pedal, the sub-functions considered include means of controlling pedal movement, pedal attachment to cable or cylinder, pedal pad design, pedal profile, ribbing pattern and pivot shaft location. Between two and five solutions are obtained for each sub-function.